1995
DOI: 10.1007/bf00262086
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nifedipine on plasma membrane fluidity and oxidative burst of polymorphonuclear leucocytes

Abstract: It has been demonstrated that the calcium antagonist nifedipine inhibits the reactive oxygen species (ROS) production by polymorphonuclear leucocytes (PMNLs) activated with phorbol myristate acetate (PMA), but the mechanism underlying this effect is still unknown. In the present study we investigated the influence of nifedipine on the PMNL plasma membrane using 1-(4-trimethylaminophenyl)-6-phenyl-1,3,5,hexatriene (TMA-DPH) fluorescence polarization (P) and on PMA- and N-formyl-methionyl-leucyl-phenylalanine (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Drug administration seems to re‐establish the energetic status of gingival cells, as they help to restore cell viability. It has been previously shown that diltiazem, nifedipine and verapamil can suppress the capacity of neutrophils in the production of oxidants (Grassi et al 1995, Feng & Hart 1996). Nifedipine has antioxidant properties reducing oxidative injury in isolated rat heart (Kauder & Watts 1996), and its protective effects on cerebral ischemia and on stroke in vivo may, in part, result from the inhibition of oxidative processes (Napoli et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Drug administration seems to re‐establish the energetic status of gingival cells, as they help to restore cell viability. It has been previously shown that diltiazem, nifedipine and verapamil can suppress the capacity of neutrophils in the production of oxidants (Grassi et al 1995, Feng & Hart 1996). Nifedipine has antioxidant properties reducing oxidative injury in isolated rat heart (Kauder & Watts 1996), and its protective effects on cerebral ischemia and on stroke in vivo may, in part, result from the inhibition of oxidative processes (Napoli et al 1999).…”
Section: Discussionmentioning
confidence: 99%